2020
DOI: 10.1186/s12871-020-01003-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of preoperative assessment of pain induced by venous cannulation in predicting postoperative pain in patients under laparoscopic nephrectomy: a prospective observational study

Abstract: Background: Postoperative pain is the most prominent concern among surgical patients. It has previously been reported that venous cannulation-induced pain (VCP) can be used to predict postoperative pain after laparoscopic cholecystectomy within 90 mins in the recovery room. Its potential in predicting postoperative pain in patients with patient-controlled intravenous analgesia (PCIA) is worth establishing. The purpose of this prospective observational study was to investigate the application of VCP in predicti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Peng et al .’s study reported that preoperative pain induced by venous cannulation and propofol infusion predicted postoperative pain after laparoscopic cholecystectomy. [ 10 ] In their study, patients with venous cannulation-induced pain with a VAS score ≥2.0 showed greater and earlier postoperative pain, and had a higher consumption of opioids as compared to those with a VAS score <2.0. The difference between the present study and Peng et al’s study[ 10 ] is the inclusion of both subjective and objective measures of pain for PIP and RIWM in the former.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peng et al .’s study reported that preoperative pain induced by venous cannulation and propofol infusion predicted postoperative pain after laparoscopic cholecystectomy. [ 10 ] In their study, patients with venous cannulation-induced pain with a VAS score ≥2.0 showed greater and earlier postoperative pain, and had a higher consumption of opioids as compared to those with a VAS score <2.0. The difference between the present study and Peng et al’s study[ 10 ] is the inclusion of both subjective and objective measures of pain for PIP and RIWM in the former.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were: (a) patients with muscular disorders, difficult venous access on the forearm, history of allergy to propofol or rocuronium, or neuromuscular diseases, (b) patients who declined to participate in this study, (c) patients who received analgesics or sedatives within the previous 24 h, and (d) menopausal patients (to exclude the hormonal effect on pain). [ 10 ]…”
Section: Methodsmentioning
confidence: 99%